Portfolio insurance investment strategies: A risk-management tool - Elma Agic-Sabeta (UTMS Journal of Economics, 2017)
Unsystemic risks in financial markets may be reduced through diversification. Systemic risks relate to the overall economy, cannot be influenced by a single company, and require special attention. Empirical research on return distributions in the long-term shows that investing under the assumption of normal distribution of returns may be dangerous. The main objectives of this article are to describe portfolio insurance strategies and investigate their advantages and disadvantages. Furthermore, their use in financial markets in both developed and emerging markets is explored, with special consideration placed on southeast European markets. Theoretical models are reviewed, including recent research articles in the field. The results are analyzed, summarized, and presented in the form of tables and graphs. The main finding of the article is identification of strategies that could be used in southeast Europe. It concludes that implementation of portfolio insurance strategies by asset managers may reduce financial risks in southeast European markets if implementation is done professionally and, simultaneously, it is monitored during the entire investment horizon.
Keywords: G11; 330; asset management; alternative investment strategies; asymmetric return profile